IMPLEMENTASI KEBIJAKAN PERMENDIKBUD NO. 33 TAHUN 2019 TENTANG MITIGASI BENCANA PADA PENDIDIKAN ANAK USIA DINI DI KABUPATEN SIDENRENG RAPPANG - Ermawati Ermawati; Andi Sinrang; Muhammad Rais Rahmat Razak; Aman Darmawan (T JDP (JURNAL DINAMIKA PEMERINTAHAN), 2026)
childhood education sector. This study analyzes the implementation of Minister of Education and Culture Regulation No. 33 of 2019 concerning Disaster-Safe Education Units (SPAB) and its effect on early childhood disaster preparedness in Sidenreng Rappang Regency. Using Edward III's policy implementation theory, this quantitative research involves 55 PAUD/kindergarten teachers through total sampling. Simple linear regression analysis shows that policy implementation significantly affects children's preparedness (β=0.950; p=0.000) with a contribution of 90.3%. The novelty of this research lies in its focus on SPAB policy implementation at the PAUD level, which is rarely studied, especially in areas with limited resource capacity. Implementation remains weak in resource aspects and bureaucratic structure. Strengthening through cross-agency coordination, special budget allocation, and continuous teacher training is essential to improve the effectiveness of SPAB programs in disaster-prone areas.